Production Stock Optimization in PEL Plant Schneider Electric Manufacturing Batam - Puji Lestari; I Gede Agus Widyadana (Jurnal Titra, 2017)
Schneider Electric Manufacturing Batam is a company in an electrical field that has an issue about inventory control; especially Stock L. Stock L is a stock of raw materials that are in the production area. This research heads on searching the optimal value of Stock L as the first step to reduce the causes and determine the suitable days of inventory for PEL. Finished goods that are on PEL control are classified into their families and the optimal value of Stock L is obtained using base stock level method and company calculation. Both these methods are not significantly different from its Two Sample T-Test result. Using base stock level, the value of Stock L can be reduced about 60.59% while using company calculation, the reduction of Stock L is about 63.42%. The suitable DIN for PEL is about 3 days.